Applying a 12-Week TRX Suspension and Plyometric Training Program: Effects on Biomotor Abilities and Physiological Adaptations in Volleyball Players - Muriyedath, Abhijith; Elayaraja, Masilamani; Salvi, Nirmal Michael; Boby, Farjana Akter; Orhan, Bekir Erhan; Astuti, Yuni; Govindasamy, Karuppasamy (Physical Education Theory and Methodology, 2025)
Background. Volleyball players require a combination of physical and physiological abilities to enhance performance, and TRX suspension and plyometric training are known to improve these abilities. However, evidence comparing their effectiveness in volleyball players is limited. Objectives. This study aimed to investigate the effects of a 12-week TRX suspension and plyometric training program on biomotor abilities and physiological adaptations in male volleyball players. Materials and methods. Forty-five male athletes (age: 21.91 ± 1.10) from Calicut University, Kerala, India, were involved in the study. The participants were divided into three groups: TRX suspension training, plyometric training, and a control group. Speed, agility, explosive power, vital capacity, and resting heart rate were measured before and after the intervention. The data were then subjected to statistical analyses, including linear mixed-effects models and repeated measures ANOVA, in order to assess group-by-time interactions. Results. The findings indicate significant improvements in speed (p < 0.001), agility (p = 0.003), and explosive power (p < 0.001) in both training groups, with notable group-by-time interactions. Vital capacity also showed substantial enhancements (p < 0.001), while resting heart rate remained unchanged. Conclusions. In conclusion, both TRX suspension and plyometric training have been revealed to be effective in enhancing biomotor abilities and vital capacity in volleyball players, making them viable options for improving performance, without affecting resting heart rate.